(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
Translating vulgarisms from one language to another poses a number of translatological problems. Vulgarisms are often only partially covered in bilingual dictionaries, which do not fully cover the context and socio-cultural factors of the use of vulgarisms. In the transmission of vulgarisms, important factors are the influence of the desemantization of vulgarisms and their recursiveness in the text, since they affect the degree of their acceptability. The process of desemantization of vulgarism "cazzo" and the Serbian lexical equivalent "kurac" did not run in parallel in Italian and Serbian. That is why the translator is called to invent vulgarisms with approximate socio-cultural acceptability. The research was conducted on translations of Federico Moche’s novel and focuses on the phraseological functions of Italian vulgarism "cazzo" and its equivalents in translations into Serbian.